Sistem Pendukung Keputusan Pemilihan Teknisi Fiber Optic Terbaik Dengan Grey Absolute Decision Analysis Methods (Studi Kasus: PT. Karya Solusi Prima Sejahtera) - Aditya Trinugraha; Taronisokhi Zebua; Anda Yanny (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2022)
PT. Karya Solusi Prima Sejahtera is a company engaged in providing professional services in the field of information technology and telecommunications. PT. Karya Solusi Prima Sejahtera also provides services for the construction of telecommunications network and information technology facilities and infrastructure. As an effort to improve the performance of fiber optic technicians at PT. Karya Solusi Prima Sejahtera carried out a performance evaluation stage and then gave rewards to fiber optic technicians who were chosen as the best. The problems that occur in determining the results of the selection of the best fiber optic technician at PT. Karya Solusi Prima Sejahtera, namely the party in charge is still making decisions based on the assessment of one party based on the subjective value of the leadership. The negative impact of this procedure is the result of decision making based on the subjective assessment of the leadership at PT. Karya Solusi Prima Sejahtera, namely the occurrence of injustice because the results of the election were not in accordance with the performance of each alternative that became a candidate for the recipient of the rewards. In an effort to overcome the above problems, in this study the authors built a decision support system for selecting the best fiber optic technician at PT. Karya Solusi Prima Sejahtera using a desktop-based programming language. The decision support system for selecting the best fiber optic technician built for PT. The work of Solusi Prima Sejahtera was carried out by applying the gray absolute decision analysis method in order to produce accurate and reliable decision outputs.